Comparative Analysis of Nutritional Components and Phytochemical Attributes of Selected Thai Rice Bran - Wisetkomolmat, Jiratchaya; Arjin, Chaiwat; Satsook, Apinya; Seel-audom, Mintra; Ruksiriwanich, Warintorn; Prom-u-Thai, Chanakan; Sringarm, Korawan (Frontiers in Nutrition, 2022)
It is important to raise awareness regarding rice's nutritional quality and health benefits in terms of enhancing rice consumption in people's daily diets. This study evaluated the proximate components and phytochemical profiles of 11 Thai rice bran varieties, 4 non-colored rice brans and 7 colored rice brans, collected from the same agricultural fields. The chemical composition (ash, fat, proteins, fiber, and gross energy) was determined using proximate analysis methods. High-performance liquid chromatography was used to analyze the γ-oryzanol, tocopherols, and anthocyanins, while gas chromatography mass spectrometry determined the free fatty compounds. The phenolic profile was determined using liquid chromatography-mass spectrometry. The results showed great variations in each parameter of the nutritional and bioactive components among different rice bran varieties. Statistical analysis was also performed correlating the results obtained from PCA to categorize the samples by their nutritional characteristics into three main groups: group A with a high content of protein and fiber, group B with a high content of fat and gross energy, and group C with low fat and energy values but high amounts of functional, active components, particularly γ-oryzanol. Anthocyanins were detected in only one sample of colored rice bran. The major free fatty acids found in rice bran samples were oleic, linoleic, and palmitic acids. Systematic assessment of the concentration of these compounds gained from this study would be helpful to the industrial sector for selecting phytochemical-rich varieties as a value-added component in nutritional products.